Effet de quelques psychotropes sur les transaminases chez les sujets en psychiatrie - Moralent Hadja, Saliha; Menad, Wissem (My University, 2022)
The burden of mental disorders continues to grow and to have a major impact on public health. Psychotropics represent the first line of therapy in the management of subjects suffering from mental disorders. The liver is the organ by which the majority of substances are metabolized, including psychotropics. There are several pharmacokinetic changes in end-stage liver disease that may interfere with the metabolism of psychotropic drugs. The present study aims to evaluate the disturbances of transaminases linked to the consumption of psychotropic drugs in the treatment of psychiatric illnesses. We carried out a prospective study which focused on 50 patients suffering from psychiatric disorders recruited in EHS in psychiatry in Mostaganem. We have measured the serum levels of liver enzymes (ALT and AST transaminases) in these patients over the past five years [2018-2022]. Our results show that plasma concentrations of transaminases increase significantly (ALAT; p=0.009 and ASAT; p=0.02) in relation to sex. The average ALT level increases by 0.2% in men and 35.77% in women, while that of AST increases up to 15.26% in men and 38.79% in women. The female sex is more sensitive. The AST level also increases significantly with age (p=0.035). Its average elevation is 5.29%, 11.44%, 26.52% and 29.27% for the age classes [24-35[, [35-46[, [46-57[and [57-68[, respectively. On the other hand, the ALT level does not vary significantly with age (p=0.54). In addition, (85%) of our population presented (AST/ALT > 1) and (60%) are > 2; which would suggest an alcoholic liver disease associated with other factors such as a history of drug addiction with viral risk, overweight, metabolic syndrome and taking hepatotoxic psychotropic drugs. Antiepileptics and antidepressants in particular (tegretol 400mg) and (laroxyl 40mg) influence the ALT level and require special attention when prescribing, especially in women and patients over 40 years old.
Keywords: psychotropics; liver; liver diseases; hepatic metabolism; transaminases; ALT; AST